ANALISIS WACANA BERITA KASUS PENCABULAN SANTRIWATI JOMBANG DI MEDIA ONLINE detik.com DAN surya.co.id EDISI 09 S.D. 11 DESEMBER 2021 - Ulfa, Maria (Spektra Komunika : Jurnal Komunikasi & Dakwah, 2023)
In this research, the aim was to analyze Teun A Van Dijk's text model in news texts related to the case of sexual assault against a female student in online media detik.com and surya.co.id. The researcher used news texts obtained from both websites as data sources. The study identified the micro-structure consisting of several elements of the news text used by both media in presenting information and to understand how media ideology is reflected in their news coverage. The results show differences in ideology between the two media in presenting news on the case of sexual assault against the female student in Jombang. This research can help in understanding how online media uses the structure of news texts to convey information and the media ideology contained within it.